Symbolic Meaning of Bugis Lontara Copying in Andi Oddang To Sessungriu: Knowledge Keepers in the Digital Era - Budiman, Muh. Agung; Muhammad Qadaruddin; Ahmad Yani (IAIN Parepare, 2025)
This study aims to reveal the symbolic significance of the Bugis Lontara copying tradition (palontara) and its subtle dakwah messages as represented in the documentary film Andi Oddang To Sessungriu: The Tale of Knowledge Preservers Enduring the Digital Age, particularly in the context of the tension between cultural preservation and the dominance of digital technology. Employing a qualitative interpretive approach with Roland Barthes’ semiotic analysis and Paul Ricoeur’s hermeneutic framework, the research examines visual motifs, narrative structures, and cinematic elements of the film, supported by in-depth interviews with director Andi Musran and protagonist-palontara Andi Oddang To Sessungriu. Findings show that everyday acts of copying dripping bamboo-pen ink, page stamping, cellakeng as divine calling, silent workspaces, and the shift from manual to digital typing are not merely technical processes but multilayered symbols connoting sincerity (ikhlas), steadfastness (istiqamah), relentless effort (reso temmangingi), honor-compassion (siri’ na pacce), mutual humanizing-strengthening (sipakatau-sipakalebbi-sipatokkong), and upright honesty (malempu). These symbols harmoniously fuse Bugis philosophical values with Islamic ethical principles, transforming the palontara figure into an exemplar of dakwah bil hal (propagation through exemplary action) and cultural jihad in the digital era. The documentary itself functions as a contemporary palontara, successfully bridging ancestral wisdom with younger generations without compromising authenticity. This research recommends that Islamic broadcasting institutions, educational bodies, and cultural activists develop more documentary-based and hybrid-media dakwah strategies that prioritize local wisdom, contemplative aesthetics, and intergenerational dialogue to counter the erosion of intangible heritage while strengthening moderate, inclusive, and contextual Islamic propagation in Indonesia.